Kajian Teologi Feminis Terhadap Tenunan Gibitir Keti dan Gibitir Merek Sebagai Media Cerita Tentang Identitas Perempuan dan Masyarakat Kolana di Kelurahan Kolana Utara Kecamatan Alor Timur - Debora Fadading; Eunike Molebila; Delila Tanaem (Jurnal Ilmiah Wahana Pendidikan, 2022)
The motifs on woven fabrics actually have deep meanings and serve as media for stories from generation to generation, but the current generation uses gibitir keti and gibitir merek weavings as clothing in traditional dances, dowries in marriages and as expressions of sympathy in mourning and other traditional events. know the meaning of these motifs.There are two purposes of this research, namely 1). to find out the meaning of the gibitir keti and gibitir merek’ woven motifs as a medium for stories about the identity of women and the people of North Kolana; and 2). to find out the study of feminist theology on gibitir keti and gibitir merek’ as a medium for stories about the identity of women and the people of North Kolana. This study uses a qualitative descriptive approach and the data analysis technique uses data presentation, data reduction, and conclusions. The results of the research are gibitir keti and gibitir merek’ weaving as media in which there are motifs that tell the identity of women and the people of Kolana.Each motif contained in the woven fabric has a deep meaning and value for a kolana woman. Thus, it can be concluded that the motifs on the gibitir keti and gibitir merek’ tell the identity of women who have existed for a long time, which were born from the ideas of women who have actually fought for their equality with Kolana men so that the position of women is not made second class. by men in a patriarchal culture.